The influence of motor abilities and some specific kinematic parameters on the results in 60 -metre hurdle-races - Brnicevic, M. M.; Babin, B.; Vlahovic, L. (Acta Kinesiologica, 2018)
The purpose of this paper is to based on measuring,determine the influences of some motor abilities and specific kinematic parameters on the result of 60m hurdle-races. For this purpose, on the sample of 9 athletes aged 13 -14, every athlete runs twice in the same conditions, and we treat every result asan entity, summary of 18 entities. In this paper athletes are competing in hurdle running, the authors of this paper, applied a set of three motor tests and two sets of specific kinematic parameters. The set of motor tests was used to assess basic motor abilities. The first set of specific kinematic parameters depicts start and start acceleration. The second set of specific kinematic parameters depicts crossing over the first hurdle. We applied regression analysis which, from the set of motor abilities, isolated standing long jump variable in addition to flying start on 20m run as significant variables, while in kinematic parameters from the first set of variables we isolated the running time from the start to the first hurdle as a variable with a significant influence, while from the second set, we isolated horizontal speed variable and body mass centre height over the hurdle. Based on the obtained results, we may draw a conclusion that the obtained results are influenced by basic motor abilities and some kinematic parameters specific in hurdle running